Humidity controlled crystallization of thin CH3NH3PbI3 films for high performance perovskite solar cell. Issue 5 (8th April 2016) - Jeong, Beomjin; Cho, Suk Man; Cho, Sung Hwan; Lee, Ju Han; Hwang, Ihn; Hwang, Sun Kak; Cho, Jinhan; Lee, Tae‐Woo; Park, Cheolmin
Abstract : Control of crystallization of a solution‐processed perovskite layer is of prime importance for high performance solar cells. In spite of the negative effect of water on perovskite solar energy conversion in several previous works, we observed that humidity plays a critical role to develop a thin uniform, dense perovskite film with preferred crystals, in particular, in a device with architecture of ITO/PEDOT:PSS/CH3 NH3 PbI3 / PC71 BM/LiF/Al fabricated by two‐step sequential spin‐coating process. Humidity controlled spin‐coating of CH3 NH3 I on the pre‐formed PbI2 layer was the most influential process and systematic structural investigation as a function of humidity revealed that grains of CH3 NH3 PbI3 perovskite crystals increase in size with their preferred orientation while film surface becomes roughened as the humidity increases. The performance of a device was closely related to the humidity dependent film morphology and in 40% relative humidity, the device exhibited the maximum power conversion efficiency of approximately 12% more than 10 times greater than that of a device fabricated at 20% humidity. The results suggest that our process with controlled humidity can be another efficient route for high performance and reliable perovskite solar cells. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : A perovskite solar cell containing a thin organic–inorganic lead halide film exhibited a reliable hysteresis‐free J – V operation with its power conversion efficiency of approximately 12.73% when the humidity was optimized at 40% during the second step spin‐coating of conventional two‐step sequential fabrication process. A smooth film consisting of numerous single crystals with minimized crystal‐to‐crystal mismatch at the grain boundaries is responsible for the high solar energy conversion.